English pronunciation by 3 years old 6 months child influenced by YouTube channel Coco Melon - Cindy Yunita Utari; Bramantya Pradipta (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2023)
Pronunciation is one of the most important part in listening, and speaking. The aims of this research were to find out the phonemes can be pronounced by 3 years old 6 months child. The data for this research was taken from the child from Jl. Mbak Likek, Desa Tarik, Sidoarjo Regency, East Java. The first 3 years old 6 months child is Bilqis. This research was applied descriptive qualitative method. The techniques for collecting the data were observation, the observation conducted for time of three month. Based on the observation, Bilqis phonemes produced 17 consonants [p, b, t, d, s, h, m, n, l, g, ŋ, w, j, ð, f, k, r], 6 short vowels [ɪ, ɛ, æ, ɒ, ʌ, ʊ], 4 long vowels [i:], [ɑ:], [ɔː], [uː], and 5 diphthongs [eɪ, aɪ, ɔɪ, əʊ, aʊ]. Furthermore, the child has pronounced most of consonants such as: bilabial consonants [p], [b], [m], labiodental [f], [v], alveolar consonants [t], [d], [s], [z], [n], [l], retroflex consonant [r], palato-alveolar consonant [tʃ], velar consonant [k], [g], [ŋ], labio-velar consonant [w] and glottal consonant [h]. As a result, the child is affected by the movie. Because of the appealing animated characters and the song's rhythm, which is well-known and simple for children to recall, this film format is generally popular with children. Parents should think about how watching cartoon films on Cocomelon's YouTube channel can expose their children to new English vocabulary.